Bacteriocin Production by Lactiplantibacillus plantarum LD1 in Solid-State Fermentation Using Lignocellulosic Substrates - Pushpa Rani; Bijender Singh; Santosh Kumar Tiwari (Fermentation)
In this study, solid-state fermentation for growth and bacteriocin production by Lactiplantibacillus plantarum LD1 was carried out using wheat bran, a lignocellulosic substrate. This is the first report showing bacteriocin production using L. plantarum LD1 in solid-state fermentation. Wheat bran supported higher production of bacteriocin (391.69 ± 12.58 AU/mL) than other substrates. Appropriate conditions were achieved using statistical designs. Significant factors identified by Plackett–Burman Design and their interactions were studied using response surface methodology. Enhanced production of bacteriocin (582.86 ± 0.87 AU/mL) and optimal growth (log10 CFU/mL 8.56 ± 0.42) were attained in wheat bran medium supplemented with peptone (1.13%), yeast extract (1.13%), glucose (1.56%), and tri-ammonium citrate (0.50%). Growth in non-optimized medium (MRS) was almost similar (log10 CFU/mL 8.15 ± 0.20), but the bacteriocin production level was lower (391.69 ± 0.58 AU/mL). Bacteriocin production was sustainable using varied quantities of wheat bran, showing the suitability of the optimized bioprocess for large-scale production. The cost for bacteriocin production in the optimized medium was found to be 444,583.60 AU/USD, which is about 4 times more economical than the cost of the commercial MRS medium, 121,497.18 AU/USD). Thus, an almost 1.5-fold improvement in bacteriocin production was achieved using wheat bran as the substrate. The cost of the production medium was reduced by approximately 25%, making the bioprocess economical.